Functionalized polystyrene nanoparticles as a platform for studying bio–nano interactions - Loos, Cornelia; Syrovets, Tatiana; Musyanovych, Anna; Mailänder, Volker; Landfester, Katharina; Nienhaus, G. Ulrich; Simmet, Thomas (Beilstein Journal of Nanotechnology, 2014)
Nanoparticles of various shapes, sizes, and materials carrying different surface modifications have numerous technological and biomedical applications. Yet, the mechanisms by which nanoparticles interact with biological structures as well as their biological impact and hazards remain poorly investigated. Due to their large surface to volume ratio, nanoparticles usually exhibit properties that differ from those of bulk materials. Particularly, the surface chemistry of the nanoparticles is crucial for their durability and solubility in biological media as well as for their biocompatibility and biodistribution. Polystyrene does not degrade in the cellular environment and exhibits no short-term cytotoxicity. Because polystyrene nanoparticles can be easily synthesized in a wide range of sizes with distinct surface functionalizations, they are perfectly suited as model particles to study the effects of the particle surface characteristics on various biological parameters. Therefore, we have exploited polystyrene nanoparticles as a convenient platform to study bio–nano interactions. This review summarizes studies on positively and negatively charged polystyrene nanoparticles and compares them with clinically used superparamagnetic iron oxide nanoparticles.
Keywords: amino groups; apoptosis; carboxyl groups; cell proliferation; leukemia cell lines; macrophages; mTOR; polystyrene nanoparticles